Factors Associated with Attitudes towards Preventing Head and Neck Cancer through HPV Vaccination in Poland: A Nationwide Cross-Sectional Survey in 2021 - Wojciech Pinkas; Mateusz Jankowski; Waldemar Wierzba (Vaccines, 2022)
Human papillomavirus (HPV) infection is a risk factor for head and neck cancers (HNC). HPV-related head and neck cancers are preventable through vaccination. This study aimed to assess the attitudes towards HPV vaccination among adults in Poland, with particular emphasis on preventing HPV-related HNC, as well as identifying factors associated with a willingness to vaccinate children against HPV. This cross-sectional survey was carried out in November 2021 on a nationwide, representative sample of 1082 adults in Poland. The computer-assisted web interview (CAWI) technique was used. Only 42.5% of respondents were aware that HPV infection is a sexually transmitted disease. Less than one fourth of respondents (23.8%) indicated vaccination as an HPV infection prevention method and 51.9% of respondents correctly indicated HPV vaccine-eligible populations. Only 48.1% of respondents declared positive attitudes towards HPV vaccinations and declared that they would vaccinate their child against HPV. Males (OR: 1.43, 95% CI: 1.11–1.85; p < 0.01), respondents who did not have children (OR: 1.50, 95% CI: 1.04–2.14; p < 0.05), as well as those who had received a higher education (OR: 1.43, 95% CI: 1.11–1.85; p < 0.01), had greater odds of indicating positive attitudes towards HPV vaccinations. This study revealed a low level of public awareness of HPV vaccination as a cancer prevention method in Poland.